posted by Karen .
If the sum of two numbers is 1 and the sum of the cubes of the numbers is 3, what is the sum of the squares of the numbers?
What if one number is zero, so the other number is ....
No, the sum of the cubes is 3 so its m+n=1 m^3+n^3=3
If you factor the second equation..
(M+n)(M^2-mn+n^2) the first term is 1, so
(m^2+n^2 -mn)=3 equation1
but if we square the first equation given
m^2+2mn+n^2 = 1
subtracting equation2 from equation1
OK, this is not making sense. Check my work, I will try again later.